2020
DOI: 10.1128/jb.00063-20
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Chromosomally Encoded Homologs of the RRNPP Protein Family in Enterococcus faecalis Biofilm Formation and Urinary Tract Infection Pathogenesis

Abstract: Enterococcus faecalis is an opportunistic pathogen capable of causing infections including endocarditis and urinary tract infections (UTI). One of the well characterized quorum sensing pathways in E. faecalis involves coordination of the conjugal transfer of pheromone-responsive plasmids by PrgX, a member of the RRNPP protein family. Members of this protein family in various Firmicutes have also been shown to contribute to numerous cellular processes including sporulation, competence, conjugation, nutrient sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…The biofilm conditions in the prior study were based on a static biofilm under nutrientrich conditions, and we were interested in knowing how RpoN and CcpA might contribute to biofilm formation under flow conditions under nutrient-poor conditions to more closely mimic the environment that is likely encountered at sites of infection. To assess the role of RpoN and CcpA in regulating biofilm formation, we quantified the level of biofilm formation under flow conditions of rpoN and ccpA mutant strains using a drip-flow bioreactor (DFBR) (28,29) in 0.1Â MM9YEGC medium (modified M9 medium supplemented with yeast extract, glucose, and casamino acids). In the absence of rpoN, there is a significant 6-fold decrease in biofilm formation relative to that of the parental V583 strain and rpoN complement, whereas in the absence of ccpA, there is a more drastic decrease in biofilm formation that is represented by an approximate 170fold decrease in biofilm formation compared to that of parental V583 or the ccpA-complemented strain (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The biofilm conditions in the prior study were based on a static biofilm under nutrientrich conditions, and we were interested in knowing how RpoN and CcpA might contribute to biofilm formation under flow conditions under nutrient-poor conditions to more closely mimic the environment that is likely encountered at sites of infection. To assess the role of RpoN and CcpA in regulating biofilm formation, we quantified the level of biofilm formation under flow conditions of rpoN and ccpA mutant strains using a drip-flow bioreactor (DFBR) (28,29) in 0.1Â MM9YEGC medium (modified M9 medium supplemented with yeast extract, glucose, and casamino acids). In the absence of rpoN, there is a significant 6-fold decrease in biofilm formation relative to that of the parental V583 strain and rpoN complement, whereas in the absence of ccpA, there is a more drastic decrease in biofilm formation that is represented by an approximate 170fold decrease in biofilm formation compared to that of parental V583 or the ccpA-complemented strain (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Biofilm formation assessment using a drip-flow biofilm reactor. A drip-flow biofilm reactor (DFBR) was utilized as previously described (28,29) to assess V583, DrpoN, DrpoN::rpoN, DccpA, and DccpA::ccpA strains for their ability to form biofilms. Briefly, the channels of the growth chamber of the DFBR were seeded with diluted overnight cultures grown in THB (1:100) in either MM9YEGC (G = 15 mM glucose) or MM9YEFC (F = 15 mM fructose) medium and incubated at 37°C for 8 h to allow initial adherence.…”
Section: Methodsmentioning
confidence: 99%
“…Nagasawa et al ( 2020 ) working with Streptococcus mutans biofilm showed that stress caused by sub‐MIC levels of antibiotics stimulated biofilm formation and this contributed to higher levels of horizontal gene transfer. This theme is reflected in the enterococci where a number of investigators have demonstrated a direct link between conjugation elements, biofilm formation and virulence (Bhatty et al, 2015 ; Parthasarathy et al, 2020 ; Schmitt et al, 2018 ). While the molecular mechanisms underlying HGT in biofilm are beginning to be elucidated there has been a shift in focus to define the impact of the process in vivo.…”
Section: Biofilm: Novel Regulation Systems and Antibiotic Resistance ...mentioning
confidence: 99%
“…Yet, the genetic diversity of RRNPP QSSs may not have been fully explored, as hinted, for instance, by the candidate receptors of E. faecalis reported to harbor local similarities with regions of Rap, PlcR, or Rgg ( Parthasarathy et al 2020 ). Hence, new communication codes as well as novel density-dependent evolutionary strategies likely await to be discovered.…”
Section: Introductionmentioning
confidence: 99%